1991
DOI: 10.1111/j.1467-954x.1991.tb02968.x
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Middle-Class Politics: A Secondary Analysis of the 1987 British General Election Survey

Abstract: In the past decade the Nuffield class schema has become the established way of operationalising social class measures in survey analyses. This paper carries out secondary analysis of the 1987 British General Election Survey to analyse the relationship between voting patterns and middle‐class groups. It argues that the Nuffield class schema actually obstructs a proper understanding of the relationship between class and politics, and that in order to develop an adequate account of middle‐class politics it is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…There is also a large difference between occupational groupings in nationalized industries (who far more support the Conservatives) and occupational groupings in the ‘real’ public sector. Savage concludes that ‘the crucial structural factor ensuring middle‐class political fragmentation lies in the different relationship of middle‐class groups towards the state’ (Dunleavy and Husbands 1985; Savage 1991: 48). Moreover, Güveli, Need and De Graaf (2003) found that the political orientation of the social and cultural specialists has become more crystallized from 1970 onwards.…”
Section: The New Middle Class and Political Orientationmentioning
confidence: 99%
“…There is also a large difference between occupational groupings in nationalized industries (who far more support the Conservatives) and occupational groupings in the ‘real’ public sector. Savage concludes that ‘the crucial structural factor ensuring middle‐class political fragmentation lies in the different relationship of middle‐class groups towards the state’ (Dunleavy and Husbands 1985; Savage 1991: 48). Moreover, Güveli, Need and De Graaf (2003) found that the political orientation of the social and cultural specialists has become more crystallized from 1970 onwards.…”
Section: The New Middle Class and Political Orientationmentioning
confidence: 99%
“…42 According to Savage, the former, whose position is secured through the possession of cultural assets, are dependent on the role of the state in the regulation of such assets, while the latter, possessors of organizational assets, are not (though they may benefit from state provision of education in fostering their children's social mobility). 43 To a substantial extent, as the analysis in Savage et al indicates, the professional/managerial division is coterminous with that between public and private sector. 44 When employment sector is controlled for, the professional/managerial split largely disappears for those in the private sector (where professionals show a high level of Conservative support comparable to that of managers) and for those in public employment (where, conversely, managers exhibit a lower level of Conservative support similar to that of professionals).…”
Section: Non-class Production and Consumption Cleavagesmentioning
confidence: 99%
“…Furthermore, Goldthorpe does not mention approximately when this consolidation of the service class will occur. Studies show that there continue to be large differences in political orientation within the service class (Brint, 1984;Kriesi, 1989;Savage, 1991;Hout et al, 1995;Brooks and Manza, 1997;De Graaf and Steijn, 1997), so it is obvious that the consolidation process of the service class is not yet finished.…”
Section: Acta Sociologica 50(2)mentioning
confidence: 99%